Modelling and characteristics of actively Q-switched Er-doped fibre laser with Tm-doped fibre saturable absorber. Issue 5 (9th March 2017) - Tao, Mengmeng; Yu, Ting; Wang, Zhenbao; Shen, Yanlong; Feng, Guobin; Ye, Xisheng
Abstract: A theoretical model concerning FSA-based active Q-switching is developed. And, characteristics of the active Q-switching operation are investigated and compared with the traditional passive Q-switching operation. Numerical results demonstrate that the active control of the repetition rate of FSA-based Q-switching is attainable. And, stable active Q-switching could be obtained from both no lasing state and stable passive Q-switching state.